Finite, fiber- and orientation-preserving group actions on totally orientable Seifert manifolds - Peet, Benjamin (Annales Mathematicae Silesianae, 2019)
In this paper we consider the finite groups that act fiber- and orientation-preservingly on closed, compact, and orientable Seifert manifolds that fiber over an orientable base space. We establish a method of constructing such group actions and then show that if an action satisfies a condition on the obstruction class of the Seifert manifold, it can be derived from the given construction. The obstruction condition is refined and the general structure of the finite groups that act via the construction is provided.